Optimal contracts for research agents. (7th February 2017) - Shan, Yaping
Abstract : We study the agency problem between a firm and its research employees under several scenarios characterized by different Research and Development (R&D) unit setups. In a multiagent dynamic contracting setting, we describe the precise pattern of the optimal contract. We illustrate that the optimal incentive regime is a function of how agents' efforts interact with one another: relative performance evaluation is used when their efforts are substitutes, whereas joint performance evaluation is used when their efforts are complements. The optimal contract pattern provides a theoretical justification for the compensation policies used by firms that rely on R&D.